2021
DOI: 10.21608/ejp.2021.61270.1022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Microorganisms on Controlling Fusarium Wilt of Roselle (Hibiscus sabdariffa L.)

Abstract: Roselle (Hibiscus sabdariffa L.) is one of the most crucial medicinal plants all over the world. The present study was carried out with the intention of solving some problems related to soil-borne diseases. Fusarium oxysporum is associated with wilt disease of roselle plant. The application of some microbiota i.e., a mixture of Pseudomonas fluorescens (PSR-11), Bacillus subtilis (BSR-8), Pleurotus ostreatus and mycorrhizeen® individually or in combination were investigated for controlling wilt disease, growth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, S. marcescens is considered nowadays as an opportunistic pathogen for healthcare-associated infection and antimicrobial resistance [64]. On the other hand, it has been demonstrated that P. fluorescens can serve as a potential biocontrol agent due to its production of a number of secondary metabolites, such as antibiotics, lytic enzymes, i.e., β-1-3 glucanase, β-1-4 glucanase, chitinase and protease [65], siderophores and hydrogen cyanide [66]. The results also show that difenoconazole was the most efficient in reducing the disease severity and AUDPC.…”
Section: Discussionmentioning
confidence: 99%
“…However, S. marcescens is considered nowadays as an opportunistic pathogen for healthcare-associated infection and antimicrobial resistance [64]. On the other hand, it has been demonstrated that P. fluorescens can serve as a potential biocontrol agent due to its production of a number of secondary metabolites, such as antibiotics, lytic enzymes, i.e., β-1-3 glucanase, β-1-4 glucanase, chitinase and protease [65], siderophores and hydrogen cyanide [66]. The results also show that difenoconazole was the most efficient in reducing the disease severity and AUDPC.…”
Section: Discussionmentioning
confidence: 99%
“…Sandy and calcareous soils represent large areas in the arid and semi-arid regions, especially in the Arab world. These soils are generally characterized by low fertility levels, easy volatilization of ammonia, low water retention capacity and alkaline effect (El-Tapey et al, 2019 andGaafar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%